Landslide dams in the Central Andes of Argentina: showing the need of revising the established landslide dam classification - Hermanns, R. L. (2006)
The Andean cordillera of Argentina is more than 3500 km long and 50 to 550 km wide and characterized by steep relief contrasts throughout. Except for a few valleys, most of this region is scarcely populated. Hence geologic mapping was mainly carried out on a scale (1:250000), which is often too small to map out various Quaternary units and therefore to highlight relations of landslide deposits with lakes or lake deposits. However, in the last years various studies have been carried out, concentrating on large landslides and their relations with valley impoundments (GONZÁLEZ DIAZ & MON, 1996; HERMANNS & STRECKER, 1999; TRAUTH & STRECKER, 1999; GONZÁLEZ DÍAZ et alii, 2000; HERMANNS et alii, 2000; TRAUTH et alii, 2000; FAUQUE et alii, 2000; FAUQUÉ & TCHILINGUIRIAN, 2002; TRAUTH et alii, 2003; HERMANNS et alii, 2003; HERMANNS et alii, 2005; FAUQUE et alii, 2005; PENNA et alii, 2005; GONZÁLEZ DÍAZ et alii, 2005). Before that, most attention was given to the catastrophic rock avalanche dam failure in the Barrancas valley causing the 1914 Río Colorado flood (GROEBER, 1916; GONZÁLEZ DÍAZ et alii, 2001; SCHUSTER et alii, 2002; HERMANNS et alii, 2004a). In this paper we will focus on two regions: one in the NW Argentine (24° - 27.5° S) and one in northern Patagonia (36° – 38° S). In both regions the authors have carried out systematic studies related to landslides with volumes in excess of 106 m3. These landslides formed at least 16 and 48 landslide dams in the two regions, respectively (Figure 1). In the following, due to the briefness of this paper, only peculiarities of the various cases will be described which will help to better understand large landslide dams in other regions as well. For the complete data set of both study areas we refer to the comprehensive paper, which will be published within the related NATO Science Series book. Likewise, we omit a setting description of the regions and refer here to the papers cited above.